2021
DOI: 10.1021/acschemneuro.1c00353
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Manifestations in COVID-19 Patients: A Meta-Analysis

Abstract: Common symptoms such as dizziness, headache, olfactory dysfunction, nausea, vomiting, etc. in COVID-19 patients have indicated the involvement of the nervous system. However, the exact association of the nervous system with COVID-19 infection is still unclear. Thus, we have conducted a meta-analysis of clinical studies associated with neurological problems in COVID-19 patients. We have searched for electronic databases with MeSH terms, and the studies for analysis were selected based on inclusion and exclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 260 publications
1
23
0
2
Order By: Relevance
“… 15 However, a meta-analysis showed that the prevalence of cerebrovascular diseases was 9.9% with a range of 6.8% to 13.4%. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 15 However, a meta-analysis showed that the prevalence of cerebrovascular diseases was 9.9% with a range of 6.8% to 13.4%. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Neurological manifestations associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or Coronavirus Disease-2019 (COVID-19) are common ( 1 ). These symptoms might be related to the central nervous system, causing dizziness, headache, seizures, ataxia, stroke, and altered consciousness, or the peripheral nervous system, such as loss of taste and smell, altered vision, and myalgia ( 2 ). Multiple pathogenesis of these neurological manifestations in COVID-19 were suggested, which are not necessarily caused by the direct effect of COVID-19 on the peripheral or central nervous system but might also occur secondary to a severe immunological reaction to viral infection ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…COVID‐19 symptoms mainly include respiratory symptoms, including fever and dry cough, with severe cases showing acute respiratory distress syndrome, infectious shock, and even death 2 . Moreover, neuroinvasive symptoms have been reported, including nonspecific symptoms (e.g., headache, fatigue, nausea), central neurological symptoms (e.g., altered mental status, sleep disorders, epilepsy, and encephalitis), and peripheral neurological symptoms (e.g., olfactory and gustatory dysfunction) 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…neuroinvasive symptoms have been reported, including nonspecific symptoms (e.g., headache, fatigue, nausea), central neurological symptoms (e.g., altered mental status, sleep disorders, epilepsy, and encephalitis), and peripheral neurological symptoms (e.g., olfactory and gustatory dysfunction). 3,4 There are abnormal imaging changes in the brain anatomy related to COVID-19, including signal abnormalities in the medial temporal lobe, 5 soft cerebral enhancement, 6 abnormalities of white matter signal, 7 and thalamic hyperactivation. 8 Brain anatomy determines the brain's ability to resist external pathogens.…”
mentioning
confidence: 99%